Follow-up do programa de psicoeducação ás familias do doente psicótico - Felicíssimo, Ana Reis (2010)
Objectivo: Avaliar o impacto do programa de intervenção psicoeducativa, ás familias do doente psicótico da Farpa (follow up). Metodologia: Escolhidas quatro familias, sendo três familias de doentes com psicose esquizofrénica e uma familia de doente com psicose neurodegenerativa mitocondrial primária. Aplicado programa de psicoeducação unifamiliar, baseado no modelo de Falloon. Estudo qualitativo. Com entrevista semi-estruturada baseada no guião elaborado para o efeito e usado gravador. Resultados: Positivos. Contribuiu para que as famílias obtivessem informação acerca da doença, relacionada com a sintomatologia, tratamento, comunicação, sinais precoces das crises, apoios da comunidade, gestão do stress e ansiedade. As familias, confirmaram os beneficios do programa na comunidade/domicílio, com agrado e adesão ao programa. Conclusões: O suporte de informações aos familiares, diminuiu o sofrimento, atenuou os niveis de stress e ansiedade e valorizou a familia como co-partícipe do tratamento e reabilitação do doente; ### ABSTRACT: FOLLOW-UP PROGRAM PSYCHOEDUCATION TO THE FAMILIES PSYCHOTIC PATIENT Objective: To evaluate the impact of a psycho educational intervention program, to the families of the psychotic patient from Farpa (follow up). Methodology: Selected four families, three of them with patients with schizophrenic psychosis and one family of patients with primary mitochondrial neurodegenerative psychosis. Applied single-family psychoeducation program, based on the model of Falloon. Qualitative study. With semi-structured interview based on the script prepared for this purpose and used the recorder. Results: Positive. Has contributed to families to obtain information about their disease-related symptoms, treatment, communication, early signs of crisis, community support, stress management and anxiety. The families have confirmed the benefits of the program in the community and particularly at home, welcome and join the program. Conclusions: The support information provide to the family members, decreased pain, attenuated the levels of stress and anxiety, and valued the family as a co-participant in the treatment and rehabilitation of the patient.